Cocoa Development Strategy and Its Influence on Productivity, Environmental Sustainability, and Farmers' Welfare (Study in Polewali Mandar District, West Sulawesi Province) - M. Yamin, H. Mujirin; Ganis Sukoharsono , Eko; Setyo Leksono, Amin; Setyowati, Endah (Accounting Department,, 2022)
Purpose - The type of this research is explanatory (confirmatory research). This type of research aims to analyze the relationship between one variable and another. Design/methodology/approach—Depending on the type of research used, hypothesis testing is carried out quantitatively using the Structural Equation Modeling (SEM) analysis approach or structural equations. Findings – Research results show that: 1. Cocoa development strategy has been empirically proven to affect cocoa productivity directly. This finding shows a significant positive influence between cocoa development strategy and productivity, 2. Empirical cocoa development strategy positively and significantly affects environmental sustainability; 3. Cocoa development strategies have a negative influence but substantially affect the farmers' welfare, 4. Empirically, cocoa productivity has a direct and negative impact on the direction of the relationship, but it is significant for environmental sustainability. The path coefficient values found that increased cocoa productivity does not increase ecological sustainability but hurts the two variables, 5. There is a positive and significant influence between cocoa productivity and farmers' welfare. Thus, this effect shows that increasing cocoa productivity will improve farmers' welfare, 6. Environmental sustainability has a positive and significant effect on the welfare of farmers, which means that an increase in environmental sustainability will increase the welfare of cocoa farmers. Thus, environmental sustainability can be a predictor of farmer welfare. Practical implications—According to empirical statistical tests, environmental sustainability has a positive and significant effect on farmer welfare. Thus, an increase in environmental sustainability will increase the welfare of cocoa farmers. Thus, environmental sustainability can be a predictor of farmer welfare. This finding is based on perception and is in line with the views of several experts. Originality/value—The path coefficient values found between the two variables indicate that the increase in cocoa productivity has no effect on increasing environmental sustainability but has a negative impact. Yet, cocoa productivity has a positive and significant influence on farmers' welfare. This effect shows that an increase in cocoa productivity will improve farmers' welfare. Keywords - development, productivity, environment, welfare, contribution Paper type – Research paper